REE, Ba, Sr and Rb abundances in some unique Antarctic achondrites - Shimizu, Hiroshi; Masuda, Akimasa (1981)
P(論文) Rare-earth elements (REE), Ba, Sr and Rb were determined for an Antarctic mesosiderite and seven Antarctic achondrites including some unique ones. The meteorite samples analyzed are Y-74450 (eucrite), Y-75032 (diogenite), ALH-77256 (diogenite), ALH-78113 (aubrite), Y-74123 (ureilite), ALH-77257 (ureilite), ALH-77005 (unique) and ALH-77219 (mesosiderite). A positive Ce anomaly (18%) is observed for Y-74450 eucrite. REE contents of Y-75032 and ALH-77256 diogenites are higher than those of Yamato recrystallized diogenites analyzed thus far. Particularly, in REE pattern of Y-75032 which is considered as intermediate between diogenites and eucrites, Leedey chondritenormalized values are 1.8-2.7. Two ureilites, Y-74123 and ALH-77257,show curved REE patterns similar to those of diogenites and inclinations of light REE slopes of these ureilites are more gentle than those observed in Kenna, Goalpara and Novo Urei ureilites. REE patterns of ALH-77219 mesosiderite and ALH-78113 aubrite are composed of some rectilinear lines, having some deviated points, respectively. Unique achondrite ALH-77005 shows an S-shaped REE pattern having positive Ce irregularity. The pattern of REE concentration ratios between ALH-77005 and Nakhla suggests a genetically intimate relationship between those two meteorites, indicative of coexisting solid-and-liquid relation. departmental bulletin paper